The Influence of Family Support on Therapy Adherence in Diabetes Patients: A Mixed-Methods Study - Veronika, Ezra Nita (International Journal on Health and Medical Sciences, 2024)
Effective management of diabetes requires consistent adherence to prescribed therapy, a process that can be significantly influenced by family support. This study explores the relationship between family support and therapy adherence in diabetes patients, aiming to provide a comprehensive understanding of how different forms of support impact disease management. A mixed-methods approach was employed, including a cross-sectional survey and in-depth interviews. The survey assessed therapy adherence using the Morisky Medication Adherence Scale (MMAS-8) and family support through a standardized scale. A sample of 300 diabetes patients was surveyed, and 30 participants were selected for qualitative interviews to explore their experiences and perceptions of family support. Quantitative analysis revealed a strong positive correlation between family support and therapy adherence. Patients who reported higher levels of emotional and practical support from their families exhibited better adherence to medication and lifestyle recommendations. Qualitative findings highlighted that supportive family interactions, such as encouragement and practical assistance, significantly contributed to effective disease management. However, the study also identified potential negative effects of over-involvement or controlling behaviors from family members, which could undermine adherence and increase patient stress.